Cytochrome P450 research and The Journal of Biological Chemistry - Guengerich, F. Peter (J Biol Chem, 2019)
In honor of the 100th birthday of Dr. Herbert Tabor, JBC's Editor-in-Chief for 40 years, I will review here JBC's extensive coverage of the field of cytochrome P450 (P450) research. Research on the reactions catalyzed by these enzymes was published in JBC before it was even realized that they were P450s, i.e. they have a “pigment” with an absorption maximum at 450 nm. After the P450 pigment discovery, reported in JBC in 1962, the journal proceeded to publish the methods for measuring P450 activities and many seminal findings. Since then, the P450 field has grown extensively, with significant progress in characterizing these enzymes, including structural features, catalytic mechanisms, regulation, and many other aspects of P450 biochemistry. JBC has been the most influential journal in the P450 field. As with many other research areas, Dr. Tabor deserves a great deal of the credit for significantly advancing this burgeoning and important topic of research.